2015
DOI: 10.7717/peerj.780
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bacterial vaginosis by a new multiplex peptide nucleic acid fluorescencein situhybridization method

Abstract: Bacterial vaginosis (BV) is one of most common vaginal infections. However, its diagnosis by classical methods reveals low specificity. Our goal was to evaluate the accuracy diagnosis of 150 vaginal samples with research gold standard methods and our Peptide Nucleic Acid (PNA) probes by Fluorescence in situ Hybridization (FISH) methodology. Also, we described the first PNA-FISH methodology for BV diagnosis, which provides results in approximately 3 h. The results showed a sensitivity of 84.6% (95% confidence i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
0
15
1
Order By: Relevance
“…Gard162 is the first PNA FISH probe designed specifically for G . vaginalis and has extensively been tested by Machado et al on a variety of cultured bacterial strains and clinical samples [ 30 , 31 ]. Using this probe, we obtained clear hybridization for all G .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gard162 is the first PNA FISH probe designed specifically for G . vaginalis and has extensively been tested by Machado et al on a variety of cultured bacterial strains and clinical samples [ 30 , 31 ]. Using this probe, we obtained clear hybridization for all G .…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of G . vaginalis , a previously described probe, Gard162 [ 30 , 31 ], was used. The broad-range bacterial probe, BacUni-1, previously designed [ 32 ] as a modified version of the broad-range eubacterial DNA probe [ 33 ], was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Then based on the criteria for BV assessment developed by Nugent et al 30 , participants with the Gram stain score of ≥7 were finally confirmed as BV ( Supplementary Table S3 ). We also probed the samples with a novel PNA-FISH probe against G. vaginalis 31 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the great diversity of vaginal microbiota in women with BV affects its potential to develop preterm birth and other negative outcomes in pregnancy ( Hyman et al, 2014 ; Nelson et al, 2015 ) and it becomes BV treatment in pregnant women a challenging task ( Haahr et al, 2016 ). Despite of its high impact, few epidemiological studies on BV have been conducted in Portugal ( Guerreiro, Gigante & Teles, 1998 ; Silva et al, 2014 ; Machado et al, 2015 ). Specifically, there is no information related to the prevalence of BV among Portuguese pregnant women.…”
Section: Introductionmentioning
confidence: 99%